Evaluation of antenatal umbilical coiling index at 16–21 weeks of gestation as a predictor of trisomy 21 and other chromosomal defects. (27th October 2013) - Verkleij, C. P. M.; van Oppen, A. C. C.; Mulder, E. J. H.; de Laat, M. W. M.; Sikkel, E.; Koster, M. P. H.; van der Tweel, I.; Franx, A.; Visser, G. H. A.
ABSTRACT: Objectives: To determine whether there is an association between sonographically assessed hyper‐ or hypocoiling of the umbilical cord and the presence of trisomy 21, to provide reference values for the antenatal umbilical coiling index (aUCI) at a gestational age of 16–21 weeks and to determine whether these measurements are reliable and reproducible . Methods: This was a prospective study of 737 pregnancies in which the aUCI was measured between 16 and 21 weeks of gestation by ultrasound at the time of amniocentesis. The aUCI was calculated as the reciprocal value of the mean length of one complete coil in centimeters. We created reference curves and studied the relationship with trisomy 21 and other chromosomal defects. In 30 pregnancies we studied the intra‐ and interobserver variation in measurements using Bland–Altman plots with associated 95% limits of agreement and intraclass correlation coefficients . Results: aUCI was found to be non‐linearly related to gestational age at 16–21 weeks and reference curves were created for the mean aUCI and the 2.3 rd, 10 th, 90 th and 97.7 th percentiles. There was no significant difference in aUCI values between the reference group ( n = 714) and cases with trisomy 21 ( n = 16) or other aneuploidies ( n = 7) (one‐way ANOVA, P = 0.716). There was good intra‐ and interobserver agreement in aUCI measurements . Conclusions: The aUCI can be measured reliably and varies according to gestational age at 16–21 weeks. The aUCI was not significantly associated with trisomy 21 or other chromosomal defects. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .